Re-examination of the Non-linear Relationship Between Management Ownership and Earnings Management: Evidence from Japan. Issue 1 (June 2017) - Mazumder, Mohammed Mehadi Masud
Abstract: The purpose of this article is to provide further evidence on the functional form of relationship between management ownership and earnings management in the Japanese context. Applying regression model with third-order polynomial likeTeshima and Shuto (2008), this study finds evidence of non-monotonic (cubic) relationship between management ownership and earnings management which supports alignment–entrenchment–alignment hypothesis. However, this study attempts to confirm the robustness of such findings with two additional approaches, namely piecewise linear regression and third-order polynomial regression with mean-centring adjustment. Unlike initial results, further evidence indicates that though the relationship between management ownership and earnings management is non-linear but the nature is quadratic ('U'-shaped) which supports alignment–entrenchment hypothesis. Such conflicting findings will surely assist the future researchers to be cautious in designing non-linear models while investigating the relationship between ownership structure and earnings management.